The impact of tumor regression grade on long-term survival in locally advanced rectal cancer treated with preoperative chemoradiotherapy. (October 2020) - Sakin, Abdullah; Sahin, Suleyman; Sengul Samanci, Nilay; Yasar, Nurgul; Demir, Cumhur; Geredeli, Caglayan; Erhan, Selma Sengiz; Akboru, Mustafa Halil; Cihan, Sener
Purpose: The aim of this study is to investigate the prognostic effect of tumor regression grade (TRG) on long-term survival in locally advanced rectal cancer treated with preoperative chemoradiotherapy. Methods: Medical records of 182 patients with locally advanced rectal cancer, who were treated with preoperative chemoradiotherapy followed by surgery between 2002 and 2016, were retrospectively reviewed. TRG was classified into five categories based on the pathological response as follows – TRG1: no viable cancer cell, TRG2: single cancer cell or small groups of cancer cells, TRG3: residual tumor outgrown by fibrosis, TRG4: residual tumor outgrowing fibrosis, TRG5: diffuse residual tumor without regression. TRG1, (TRG2+TRG3), and (TRG4+TRG5) were grouped as complete response, intermediate response, and no response, respectively. Results: Of the 182 patients with locally advanced rectal cancer, 112 (61.5%) were male. The mean age was 54.4 (range, 25–87) years. The total number of patients in complete response, intermediate response, and no response group was 24 (13.2%), 105 (57.7%), and 53 (29.1%), respectively. The corresponding five-year relapse-free survival and overall survival rates were 79.8%–92.3%, 74.7%–79.4%, and 55.7%–55.8%, respectively (p < 0.05 for relapse-free survival, p < 0.05 for overall survival). According to ypTNM stage, there was no significant difference in relapse-free survival among TRG groups in ypStage I and II patients (p > 0.05). In ypStage III patients, relapse-free survival was 62 months in no response group vs. not reached in intermediate response group (p < 0.05). According to the ypTNM, there was no significant difference in overall survival among TRG groups in ypStage I, II, and III patients (p > 0.05). In the multivariate analysis, pathological complete response was found to be an independent variable for relapse-free survival and overall survival (hazard ratio (95% confidence interval), 0.34 (0.17–6.77), 0.39 (0.18–0.83), respectively). Conclusion: This study showed that patients with pathological complete response to preoperative chemoradiotherapy had longer relapse-free survival and overall survival rates than those with residual disease.